2005
DOI: 10.1152/ajpgi.00268.2004
|View full text |Cite
|
Sign up to set email alerts
|

COOH-terminal 26-amino acid residues of progastrin are sufficient for stimulation of mitosis in murine colonic epithelium in vivo

Abstract: Transgenic mice (hGAS) that overexpress human progastrin are more susceptible than wild-type mice (FVB/N) to the induction of colonic aberrant crypt foci (ACF) and adenomas by the chemical carcinogen azoxymethane. We have previously shown significantly increased levels of colonic mitosis in hGAS compared with FVB/N mice after gamma-radiation. To investigate whether the effects of progastrin observed in hGAS colon require the presence of other forms of circulating gastrin, we have crossed hGAS (hg(+/+)) with ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
4
26
1
Order By: Relevance
“…One possibility is that CCK2R is a direct downstream target of progastrin, and indeed receptor mRNA expression was upregulated in hGAS /+ colon. On the other hand, our previous studies with hGAS /+ /GAS knockout mice have shown that progastrin is able to stimulate colonic proliferation in the absence of amidated gastrin (12), which is contradictory to another report (13). Formally, another possibility is that CCK2R deficiency results in a dominant inhibitory cancer phenotype independent of progastrin effects.…”
Section: Figurecontrasting
confidence: 64%
See 1 more Smart Citation
“…One possibility is that CCK2R is a direct downstream target of progastrin, and indeed receptor mRNA expression was upregulated in hGAS /+ colon. On the other hand, our previous studies with hGAS /+ /GAS knockout mice have shown that progastrin is able to stimulate colonic proliferation in the absence of amidated gastrin (12), which is contradictory to another report (13). Formally, another possibility is that CCK2R deficiency results in a dominant inhibitory cancer phenotype independent of progastrin effects.…”
Section: Figurecontrasting
confidence: 64%
“…Furthermore, progastrin overexpression or exogenous administration could maintain colonic epithelial mitosis after DNA damage by γ irradiation or chemical carcinogens (11). These effects of progastrin were not dependent on other forms of gastrin, since progastrin-expressing hGAS mice showed a similar phenotype when crossed with a gastrin knockout background (12). Nevertheless, there has been a report on increased azoxymethane-induced (AOM-induced) carcinogenesis in GAS knockout mice (13), in contrast to our findings of decreased colonic proliferation, polyposis, and prolonged survival when crossed to Apc/Min mice (14,15).…”
Section: Introductionmentioning
confidence: 98%
“…The larger precursor 80 amino acid progastrin peptide also stimulates proliferation of colon cancer cell lines , inhibits pancreatic cancer apoptosis (Rengifo-Cam et al 2007), and transgenic mice over-expressing progastrin exhibit colonic hyperproliferation, increased mitosis after irradiation and adenomata and carcinomas after exposure to the chemical carcinogen azoxymethane (Cobb et al 2004, Ottewell et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…PG, GG and G17 exert proliferative effects on normal and cancerous gastrointestinal (GI) cells in vitro and in vivo (Wang et al, 1996;Hollande et al, 1997;Koh et al, 1999;Baldwin et al, 2001;Brown et al, 2003;Singh et al, 2003;Ottewell et al, 2005). PG and GG exert cocarcinogenic effects on colon carcinogenesis in response to azoxymethane (Singh et al, 2000a, b;Aly et al, 2001;Cobb et al, 2004).…”
Section: Introductionmentioning
confidence: 99%